Case Report: Painful left bundle branch block syndrome complicated with vasovagal syncope - Jiangying Luo; Yajun Xue; Fang Liu; Jing Yang; Boda Zhou; Ping Zhang (Frontiers in Cardiovascular Medicine)
BackgroundPainful left bundle branch block (LBBB) syndrome is an uncommon disease that is defined as intermittent episodes of angina associated with simultaneous LBBB changes on an electrocardiogram (ECG) with the absence of flow-limiting coronary artery disease or ischemia on functional testing. Vasovagal syncope (VVS) is the most common cause of syncope and can be provoked by sublingual nitroglycerin (NTG). Herein, we report a case of painful LBBB syndrome complicated with VVS, which was misdiagnosed as acute coronary syndrome and cardiogenic shock.Case summaryA 62-year-old woman presented with intermittent exertional chest pain for 3 years and deteriorated for 2 weeks. An ECG, transthoracic echocardiography, and laboratory test results were all normal. Exercise treadmill testing induced chest pain, accompanied by new-onset LBBB. She fainted after finishing the test and receiving sublingual NTG, with a rapid decline in heart rate and blood pressure, which was relieved by 0.5 mg of atropine administered intravenously. Coronary angiography showed no evidence of obstructive lesions. Isoprenaline stress echocardiography induced chest pain and rate-dependent LBBB and showed interventricular/intraventricular desynchrony simultaneously. A head-up tilt test verified mixed VVS in the provocative phase. A diagnosis of painful LBBB syndrome complicated with VVS induced by sublingual NTG was made. The patient received an extended-release metoprolol succinate tablet and had no symptoms at a 1-year follow-up.ConclusionPainful LBBB syndrome is an uncommon cause of chest pain and is often overlooked by physicians. Misdiagnosis and mistreatment of painful LBBB syndrome may even cause secondary damage, such as VVS induced by sublingual NTG, which is usually used to alleviate angina.